Considerações sobre planejamento de eclusagens na hidrovia Tietê-Paraná - Silva, Haroldo [UNESP] (2015)
The lock system of Tietê-Paraná waterway enables vessels diferent levels formed by the dams of hydroelectric power plants, built with the purpose of multiple use water, which enables the transport of passengers and goods, integrating this waterway as an important transport corridor of the São Paulo'state. The aim of this study is to identify the key variables that influence the operations of locking process and analyze their effects on the performance of shipping. The selected variables were used in the case study at the Barra Bonita, Bariri, Ibitinga, Promissão and Nova Avanhandava's locks, attached to the hydroelectric power plants at same name, to verify through a questionnaire, observation and document analysis, the influence of these variables on the overall performance of navigation. The locks operate 24 hours a day throughout the year and have their operations interrupted every two years, for a period of 30 days to perform preventive maintenance on the equipments. This practice has been very important for locks, historically, reaching average levels of availability of 99% per year, contributing to modal attractiveness. The demand for this waterway, an important factor for the balance of the country'cargo transportation matrix, causes formation of queues of vessels at loocks, in some periods of the day, actually occurred frequently until the month of may 2014. Thus, this work contributes indicating the leading cause of queuing in locks, and suggests the adoption of systematic procedures for loocking process, as a means to organize the vessel's traffic and increase the productivity of companies that operates in a Tiete-Paraná waterway